Daylight PDT with MAL: current data and practical recommendations of an expert panel - Philipp‐Dormston, Wolfgang G.; Karrer, Sigrid; Petering, Holger; Ulrich, Claas; Dirschka, Thomas; Berking, Carola; Lonsdorf, Anke Susanne; Gerber, Peter Arne; Radakovic, Sonja; Hunger, Robert E.; Szeimies, Rolf-Markus (Journal der Deutschen Dermatologischen Gesellschaft, 2015)
Photodynamic Therapy (PDT) is one of the standard treatment modalities for actinic keratoses (AKs). Daylight PDT (DL-PDT) with MAL cream is a rather recent development, which, instead of an artificial light source, uses daylight for the activation of the photosensitizer. The present review summarizes available data based on a selective literature search, highlights practical aspects, and reflects the authors’ expert knowledge in using DL-PDT. With respect to efficacy, study data shows that DL-PDT is noninferior to conventional PDT (cPDT). However, given that DL-PDT is markedly less painful, it is significantly better tolerated than cPDT. In Europe, DL-PDT can be performed from March to October, on sunny as well as on cloudy days. UV protection of untreated areas of the body should be observed. Outside temperature should not fall below 10°C. On hot days, patients should be advised to stay in the shade if necessary. Representing a useful addition to current therapeutic options, DL-PDT with MAL cream is, among others, suitable for patients with field cancerization and/or those who have experienced severe pain associated with cPDT.
Gesehen am 06.07.2020